Legal Perspective on Civil Remedies in the Malaysian Securities Industry - Yeon, Asmah (JPAIR Multidisciplinary Research, 2013)
Malaysia’s capital market has performed well in 2009 and this is reflected from the Malaysia’s biggest rise of capital in the form of Maxis Bhd’s RM11.2 billion of initial public offering in 2009. Nevertheless, self-interests may create behaviors that pose risks to the safety of investors and the integrity of markets. Therefore, the Malaysian Securities Commission (SC) implemented a civil action against the offender of securities crimes in order to protect investors and to cover losses faced by investors because of securities crimes. The objective of this paper is to discuss and analyze the law and enforcement of civil action in securities industry in Malaysia. This is a legal research and involved examining legal data such as statutes and court cases. The Capital Markets and Services Act 2007(CMSA 2007) regulate matters relating to the activities, markets and intermediaries in the capital markets. The CMSA 2007 provides provisions relating to civil remedies to the victims of securities crimes and further empowers the SC to enforce administrative and civil actions. The analysis on enforcement of civil actions of SC shows that the outcome of the said strategy is very encouraging and accepted well by the industry player.
Keywords: securities law; civil action; legal research; Malaysia